The Effect of Career Development, Organizational Commitment, and Work Motivation on Employee Performance: Pengaruh Pengembangan Karir, Komitmen Organisasi, dan Motivasi Kerja Terhadap Kinerja Karyawan - Setiawan, Andika Agus; Adji, Kumara (Indonesian Journal of Law and Economics Review, 2022)
This study aims to determine the effect of career development, organizational commitment and work motivation employee performance at CV. Farmer's Bracelet. This research uses quantitative methods. Sources of data used through primary data and secondary data. The data collection technique used a questionnaire which was distributed through a questionnaire. The sampling technique in this study is probability sampling technique and simple random sampling using the slovin formula for employees of CV. Bracelet Tani, with a total of 159 respondents. The results showed that: (1) Career Development (X1), Organizational Commitment (X2), and Work Motivation (X3) simultaneously affect Employee Performance (Y) on CV. Bracelet Tani. This conclusion is based on the results of the F test which shows Fcount t table and the significance value is less than 0.05 so that the first hypothesis proposed is proven true. (2) Career Development (X1), Organizational Commitment (X2), and Work Motivation (X3) partially affect Employee Performance (Y) on CV. Farmer's Bracelet. This conclusion is based on the results of the t test which shows that tcount ttable and the significance value is less than 0.05 so that the second hypothesis proposed is proven true. (3) Career Development (X1) is a variable that has a dominant influence on Employee Performance (Y) on CV. Farmer's Bracelet. This conclusion is based on the value of tcount and the value of standardized of coefficients Beta is the largest compared to the variables of Organizational Commitment (X2) and Work Motivation (X3). Keywords: Career Development; Organizational Commitment; Work motivation; Employee performance